Milk and dairy products consumption and the risk of oral or oropharyngeal cancer: a meta-analysis. Issue 12 (16th December 2019) - Yuan, Jian; Li, Wen; Sun, Wei; Deng, Shuli
Abstract: The present meta-analysis was conducted to explore the role of milk and dairy products consumption on oral or oropharyngeal cancer risk. PubMed, Embase and Chinese Wanfang databases were investigated until 30 June 2019. The overall and subgroup associations were pooled with odds ratios (ORs) and 95% confidence intervals (CIs). As a result, the present study involving 4635 cases and 50777 participants from 12 publications suggested that an inverse association was found between milk and dairy products consumption and oral or oropharyngeal cancer risk (OR = 0.74, 95% CI = 0.59–0.92; I 2 = 65.9%, P for heterogeneity =0.001). Four studies reported milk consumption on oral cancer risk, but no significant association was found (OR = 0.91, 95% CI = 0.61–1.37). Six studies about milk consumption and oropharyngeal cancer risk found that there was a positive association between them (OR = 0.63, 95% CI = 0.44–0.90). In conclusion, findings from our meta-analysis indicated that milk and dairy products consumption may be associated with decreased risk of oral or oropharyngeal cancer.